European Automated Container Terminals - Andrej David; Jarmila Sosedova; Lisa-Maria Putz; Natalija Jolic; Zvonko Kavran (Communications - Scientific letters of the University of Zilina, 2014)
The establishment of the container as a cargo packaging unit belongs to the most significant developments in maritime transport in the 20th century. Containers started to be used in sea transport due to the reduction of loading time. They also protect cargo against its damage, theft and loss [1]. Containers are transported by specialized cellular container ships that are classified into the generations depending on their size. The role of the container terminals is to handle, load, unload, and transfer containers by special equipment. There is also a yard where containers are stored [2] and [3]. Congested container sea ports have implemented new ways how to increase their throughput. The construction of automated container terminals is one way how to do it.